2013
DOI: 10.1038/nphoton.2013.47
|View full text |Cite
|
Sign up to set email alerts
|

Spectral compression of single photons

Abstract: Photons are critical to quantum technologies since they can be used for virtually all quantum information tasks: in quantum metrology, as the information carrier in photonic quantum computation, as a mediator in hybrid systems, and to establish long distance networks. The physical characteristics of photons in these applications differ drastically; spectral bandwidths span 12 orders of magnitude from 50 THz for quantum-optical coherence tomography to 50 Hz for certain quantum memories. Combining these technolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 35 publications
3
102
0
Order By: Relevance
“…As mentioned previously, the large timing jitter ( 200 ps for APDs) of efficient photon-counting detectors makes it challenging to resolve the temporal correlations directly. Instead, we propose to implement measurements in the time basis by sending each photon through a time-to-frequency converter [47,48,49]. As shown in Fig.…”
Section: The Protocolmentioning
confidence: 99%
“…As mentioned previously, the large timing jitter ( 200 ps for APDs) of efficient photon-counting detectors makes it challenging to resolve the temporal correlations directly. Instead, we propose to implement measurements in the time basis by sending each photon through a time-to-frequency converter [47,48,49]. As shown in Fig.…”
Section: The Protocolmentioning
confidence: 99%
“…Quantum temporal imaging can borrow many ideas and techniques from its spatial counterpart. Several approaches to the quantum temporal imaging at the single-photon level have been published in the last decade [24,25,26,27], but the case of continuous variables has been considered only recently [28]. It has been shown that having a squeezed light as the object imposes additional constraints on the temporal imaging system, if one aims at preserving the quantum structure of the object, namely, its degree of squeezing.…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic feature has led to the development of a variety of techniques for spectral and temporal manipulations of single photons [5][6][7][8][9][10][11][12]. Recently, spectral compression of photons has gained widespread attention in order to efficiently interface wide-band sources of correlated photons with narrow-band nodes of a quantum network, for example, quantum dots and atomic systems [11,[13][14][15]. At the same time, temporal magnification of photons facilitates high-fidelity photonic measurements in quantum simulations [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%